Finance and Development, June 1964. (Finance and Development; Finance and Development, 1964)
This paper describes the origin of the IMF, its organization, and its method of working. The IMF has as its aim the economic prosperity of the whole world. The IMF pursues an active program of economic research. For this purpose, it systematically collects and publishes data on international trade, holdings of gold and foreign currencies, national income, price indices, restrictions on international payments, international movements of capital, and so on. All this is part of the background against which discussions of problems of individual members are carried out by the Executive Board.